"It's like Taking Your Man Card Away": Male Victims' Narratives of Male-to-Male Sexual Harassment. Issue 5 (20th October 2018) - Scarduzio, Jennifer A.; Wehlage, Shane J.; Lueken, Sarah
Abstract : Sexual harassment is a serious organizational problem. Despite the burgeoning of research over the past 30 years, there has been less attention provided to male victim voices. The current study qualitatively explores the experiences of two male victims of sexual harassment who were harassed by male perpetrators. The study explores the interplay of uncertainties, threats, and negotiation of masculine, heterosexual identities. We also highlight the differences and similarities between the men's communication practices during what we call the build up, the realization, and others' responses to the men's narratives. Theoretical implications are offered for hegemonic masculinity and liminality in relation to the experiences of male victims.